THE INFLUENCES OF POWER VARIATIONS ON SELECTIVITY OF SYNTHESIS REACTION OF 2’-HYDROXYCHALCONE ANALOGUE UNDER MICROWAVE IRRADIATION - Adel Zamri; Hilwan Yuda Teruna; Ihsan Ikhtiarudin (Molekul, 2016)
Some 2’-hydroxychalcone analogues have been widely used as an intermediate to synthesize various heterocyclic compounds, such as flavanones, flavanonols, flavones, flavonols and others. The heterocyclic compounds are also known to have a variety of interesting bioactivities in the medicinal chemistry and also have potency to be applied  in material chemistry including in industry. Therefore, 2’-hydroxychalcone analogues are often synthesized by researchers as intermediate, both in research associated with drug discovery and material synthesis. The aim of this study is to investigate the effect of microwave irradiation power variations on the selectivity of reaction of 2’-hydroxychalcone analogue synthesis. The variations of power that have been used in this study were 100, 180, 300 and 450 W with using a domestic microwave. Based on the study, we conclude that the power variation of microwave irradiationwere proven to effect the selectivity of synthesis reaction. In this study, the most suitable irradiation power to be applied on this synthesis is 180 W.